Effect of body condition score before calving on selected reproductive traits in holstein dairy cows - Yildiz, Atilla (Ataturk Universitesi, 2016)
In the present study, it was investigated the relationship between reproductive performance and body condition score (BCS) around calving in healthy Holstein dairy cows. Body condition was assessed according to the 5-point BCS system with 0.25 unite increments. To determine the effect of BCS on selected reproductive triats, cows were divided into three groups based on their BCS in antepartum period; Group 1 (BCS ?3.25; n=27); Group 2 (BCS 3.5-3.75; n= 68); and Group 3 (BCS ?4; n=23). Significant differences between the groups were observed considering calving to first insemination interval and service period. The calving to first insemination interval and the service period were shorter for the cows in Group 2 than for the cows in Group 1 and Group 3 (P < 0.05). The pregnancy rate at in the first insemination for the cows in Group 2 was 1.4 and 1.8 fold higher than the cows in Group 1 and Group 3, respectively. The highest reproductive performance was achieved in cows with body condition ranging between 3.5 and 3.75. Therefore, it was concluded that the reasonable BCS at near calving around calving for Holstein cows were 3.5-3.75 body condition.
Holştayn Sütçü Ineklerde Buza?ilamadan Önceki Vücut Kondisyon Skorunun Seçilen Döl Verimi Özellikleri Üzerine Etkisi
Keywords: Ante-partum; Body condition score; Reproductive performance; Service period